2014
DOI: 10.3389/fphys.2014.00101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute resistance exercise on carotid artery stiffness and cerebral blood flow pulsatility

Abstract: Arterial stiffness is associated with cerebral flow pulsatility. Arterial stiffness increases following acute resistance exercise (RE). Whether this acute RE-induced vascular stiffening affects cerebral pulsatility remains unknown. Purpose: To investigate the effects of acute RE on common carotid artery (CCA) stiffness and cerebral blood flow velocity (CBFv) pulsatility. Methods: Eighteen healthy men (22 ± 1 yr; 23.7 ± 0.5 kg·m−2) underwent acute RE (5 sets, 5-RM bench press, 5 sets 10-RM bicep curls with 90 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 59 publications
6
27
2
Order By: Relevance
“…A cross‐sectional study by Nakamura and Muraoka () revealed increased MCA pulsatility with concurrent reduced central arterial compliance in resistance‐trained individuals. This appears to be a chronic adaptation as untrained individuals demonstrated no change in MCA pulsatility following resistance exercise, despite an increase in common carotid artery pulse pressure (Lefferts, Augustine, & Heffernan, ). Windkessel models of the cerebral circulation indicate that reductions in cerebral vessel compliance reduce TFA‐derived gain (Zhang, Behbehani, & Levine, ), indicating compliance is a modulator of cerebral autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…A cross‐sectional study by Nakamura and Muraoka () revealed increased MCA pulsatility with concurrent reduced central arterial compliance in resistance‐trained individuals. This appears to be a chronic adaptation as untrained individuals demonstrated no change in MCA pulsatility following resistance exercise, despite an increase in common carotid artery pulse pressure (Lefferts, Augustine, & Heffernan, ). Windkessel models of the cerebral circulation indicate that reductions in cerebral vessel compliance reduce TFA‐derived gain (Zhang, Behbehani, & Levine, ), indicating compliance is a modulator of cerebral autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of how arterial wall mechanics change during an acute bout of resistance exercise, when blood pressure is significantly elevated, might provide insight into the mechanisms responsible for the increase in arterial stiffness previously reported (Lefferts et al. ). This is of particular importance in the CCA, as the brain is extremely susceptible to hemodynamic pulsatility (Hirata et al.…”
Section: Introductionmentioning
confidence: 93%
“…CCA arterial stiffness is also known to increase following an acute bout of resistance exercise (Lefferts et al. ). Despite this, and the well‐known impact of acute resistance exercise on arterial hemodynamics, the effect of an acute bout of resistance exercise on CCA wall mechanics is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Because aerobic and stretching exercises are characterized by efficient cardiorespiratory functioning (e.g., Mazzeo et al, 1998; Seifert and Secher, 2011; Zheng et al, 2015) and improved cognitive control (e.g.,Voss et al, 2010; Erickson et al, 2015), we expect that engaging in these types of exercise should enable people to exert greater self-control over grudges (Pontifex et al, 2011; Burnette et al, 2014; Erickson et al, 2014; Audiffren and Andre, 2015). In comparison, because anaerobic exercise is defined by short bursts of extremely high energy that limits cardiorespiratory functioning (Jung et al, 2012; Lefferts et al, 2014) and cognitive control (e.g., Chang et al, 2012b), we propose that engaging in this form of exercise should limit self-control over grudges (Oaten and Cheng, 2006; Pontifex et al, 2011). Moreover, we predicted that one downstream gain for victims of transgressions who engage in aerobic and stretching exercises would be greater forgiveness than those who engage in anaerobic exercises.…”
Section: Introductionmentioning
confidence: 99%